2018
DOI: 10.1093/sleep/zsy133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computerized methods for rapid eye movement sleep without atonia detection

Abstract: Rapid eye movement (REM) sleep without atonia detection is a prerequisite for diagnosis of REM sleep behavior disorder (RBD). As the visual gold standard method is time-consuming and subjective, several automated methods have been proposed. This study aims to compare their performances: The REM atonia index (RAI), the supra-threshold-REM-activity metric, the Frandsen index, the short/long muscle activity indices, and the Kempfner index algorithms were applied to 27 healthy control participants (C), 25 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…To overcome these problems, several computerized methods have been developed and these include the REM atonia index (RAI) (Ferri et al, 2010(Ferri et al, , 2008, the supra-threshold REM activity metric (Burns et al, 2007), the short/long muscle activity index (Guttowski et al, 2018;Mayer et al, 2008), the Frandsen index (FRI) (Frandsen et al, 2015), the Kempfner index (KEI) and the computerized version of the SINBAR method (Frauscher et al, 2014). In a previous study, we compared the performances of these methods (except the computerized SINBAR due to lack of important implementation details in the original published description) in identifying RBD in different scenarios and we concluded that none of the methods could be elected as the optimal one, due to the varying performances of the methods across the different scenarios (Cesari et al, 2018b). However, we found that RAI, FRI and KEI achieved generally higher performances than the others (Cesari et al, 2018b).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…To overcome these problems, several computerized methods have been developed and these include the REM atonia index (RAI) (Ferri et al, 2010(Ferri et al, , 2008, the supra-threshold REM activity metric (Burns et al, 2007), the short/long muscle activity index (Guttowski et al, 2018;Mayer et al, 2008), the Frandsen index (FRI) (Frandsen et al, 2015), the Kempfner index (KEI) and the computerized version of the SINBAR method (Frauscher et al, 2014). In a previous study, we compared the performances of these methods (except the computerized SINBAR due to lack of important implementation details in the original published description) in identifying RBD in different scenarios and we concluded that none of the methods could be elected as the optimal one, due to the varying performances of the methods across the different scenarios (Cesari et al, 2018b). However, we found that RAI, FRI and KEI achieved generally higher performances than the others (Cesari et al, 2018b).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…For RBD detection, several automated algorithms have been proposed (Ferri et al., , ; Frandsen et al., ; Frauscher et al., ; Kempfner & Nikolic, ; Mayer et al., ) and compared (Cesari et al., ). The algorithm described in Frauscher et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in ambulatory sleep monitoring devices and signal analysis methods may allow for measurement of RSWA at home over multiple nights or longitudinally. 114 There is no clearly superior method of RSWA quantification, 115 but consistent application of a single method-particularly one with multicentre comparisons and validations-would be required to use RSWA as an outcome marker.…”
Section: Sleep Disordersmentioning
confidence: 99%